Harold Leventhal papers - Leventhal, Harold, 1915-1979.
Chiefly correspondence, case files, notebooks and notes, and office files documenting Leventhal's service as judge on the U.S. Court of Appeals for the District of Columbia Circuit. Also includes personal correspondence, files from the law firm Ginsburg and Leventhal, in Washington, D.C., speeches and writings, and other papers. Documents his service as visiting judge for the United States Court of Appeals for the 2nd Circuit, as a member of the prosecution staff for the Nuremberg War Crime Trials, and with the U.S. Office of Price Administration, and his appointment as a visiting lecturer at Yale University. Subjects include administrative, constitutional, and criminal law appeals; rate-making theory for American Telephone and Telegraph Company; the Democratic National Committee; and Democratic National Convention in Atlantic City, N.J., 1964; Mississippi Freedom Democratic Party; government sponsorship of the nativity scene in the Christmas pageant of peace near the White House in Washington, D.C.; and the Watergate trial.
Correspondents include Walter M. Bastian, David L. Bazelon, Warren E. Burger, John Anthony Danaher, Kirk Douglas, Charles Fahy, David Ginsburg, Lyndon B. Johnson, John F. Kennedy, Louis Lusky, Carl McGowan, Harriet F. Pilpel, Stanley Forman Reed, John J. Sirica, Simon Ernest Sobeloff, Harlan Fiske Stone, Edward A. Tamm, and J. Skelly Wright.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Lawyer and jurist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bastian, Walter M. -- 1891-1975 -- Correspondence; Bazelon, David L. -- Correspondence; Burger, Warren E., -- 1907-1995 -- Correspondence; Danaher, John Anthony, -- 1899- -- Correspondence; Douglas, Kirk, -- 1916- -- Correspondence; Fahy, Charles, -- 1892-1979 -- Correspondence; Ginsburg, David, -- 1912-2010 -- Correspondence; Jesus Christ -- Nativity; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kennedy, John F. -- 1917-1963 -- Correspondence; Lusky, Louis -- Correspondence; McGowan, Carl, -- 1911-1987 -- Correspondence; Pilpel, Harriet F. -- Correspondence; Reed, Stanley Forman, -- 1884-1980 -- Correspondence; Sirica, John J. -- Correspondence; Sobeloff, Simon Ernest, -- 1894-1973 -- Correspondence; Stone, Harlan Fiske, -- 1872-1946 -- Correspondence; Tamm, Edward A. -- 1906- -- Correspondence; Wright, J. Skelly -- Correspondence; United States. -- Court of Appeals (2nd Circuit); United States. -- Court of Appeals (District of Columbia Circuit); United States. -- Office of Price Administration; American Telephone and Telegraph Company; Democratic National Committee (U.S.); Ginsburg and Leventhal; Mississippi Freedom Democratic Party; Yale University; Administrative law -- United States; Christmas; Constitutional law -- United States; Criminal law -- United States; Local transit -- Fares -- Washington (D.C.); Nuremberg War Crime Trials, Nuremberg, Germany, 1946-1949.; Pageants -- Washington (D.C.); Practice of law -- Washington (D.C.); Telephone -- Rates -- United States; War crime trials -- Germany; Watergate Trial, Washington, D.C., 1973.; Jurists; Lawyers